Nilai Pendidikan Islam Bagi Karakter Generasi Muda dalam Novel Kami (Bukan) Sarjana Kertas - Salwa Zalzabilah; Riza Wardefi (An-Nuha, 2026)
Islamic education in the novel "We Are (Not) Paper Scholars" by J.S. Khairen. In addition, this study analyzes the relevance of these values ​​in shaping the character of the younger generation. The method used is qualitative with a content analysis approach. Data were collected through intensive reading and recording of quotations related to Islamic educational values. The quotations were then categorized and analyzed based on Islamic character education theory. The results show that this novel contains core values, such as religiosity, honesty, hard work, responsibility, discipline, empathy, and social solidarity. These values ​​are highly relevant to shaping the character of the younger generation, especially in facing moral, social, and cultural challenges in the modern era. Therefore, this novel can serve as an alternative medium for Islamic-based character education.